Hybridized bio-inspired intrusion detection system for Internet of Things - Singh, Richa; Ujjwal, R. L. (Frontiers in Big Data, 2023)
The Internet of things(IoT) consists of several smart devices equipped with computing, sensing, and network capabilities, which enable them to collect and exchange heterogeneous data wirelessly. The increasing usage of IoT devices in daily activities increases the security needs of IoT systems. These IoT devices are an easy target for intruders to perform malicious activities and make the underlying network corrupt. Hence, this paper proposes a hybridized bio-inspired-based intrusion detection system (IDS) for the IoT framework. The hybridized sine-cosine algorithm (SCA) and salp swarm algorithm (SSA) determines the essential features of the network traffic. Selected features are passed to a machine learning (ML) classifier for the detection and classification of intrusive traffic. The IoT network intrusion dataset determines the performance of the proposed system in a python environment. The proposed hybridized system achieves maximum accuracy of 84.75 % with minimum selected features i.e. 8 and takes minimum time of 96.42 sec in detecting intrusion for the IoT network. The proposed system’s effectiveness is shown by comparing it with other similar approaches for performing multiclass classification.